Technically Speaking: Technical Skills Needed for Agricultural Communication Baccalaureate Graduates - Arthur Leal; Kati M Lawson; Ricky W Telg; Joy N Rumble; Nicole LaMee Perez Stedman; Debbie Treise (Journal of Applied Communications, 2020)
Technically Speaking: Technical Skills Needed for Agricultural Communication Baccalaureate Graduates Abstract The purpose of this national study was to assess the perceived importance of 57 technical skills identified in previous literature, and to determine entry-level, agricultural communication graduates’ ability to perform those technical skills as perceived by agricultural communication graduates, communication industry professionals, and agricultural communication faculty members. Participants from the three evaluation groups (n = 193) identified three of the most important technical skills needed by agricultural communication graduates. These skills were communicating in written form, concise and clear writing, and communicating verbally. Graduates placed a higher importance on technical skills than the other two evaluation groups. All three evaluation groups showed some agreement on graduates’ highest ability to perform several technical skills: ability to use technology, ability to use Microsoft Word, and ability to adapt to contemporary media. A significant difference was found between the evaluation groups for the ability graduates afforded themselves in telephone etiquette, ability to use Microsoft Word, reading skills, ability to use Instagram, ability to use graphic design software, and ability to use web design software, as compared to the other two evaluation groups. Recommendations included incorporating technical skills into instruction for undergraduate students. Content should be focused in technical-skill areas identified as being of high importance: communicate in written form; communicate verbally; write concisely and clearly; and use of proper punctuation, grammar, and spelling. Faculty members could benefit from research that identifies more effective measures to evaluate technical skills attainment.
Keywords: Technical skills; agricultural communication; program evaluation